Environmental justice: who's moving forward and who's being left behind? - Balietti, Anca; Zeising, Tom (Ruperto Carola, 2025)
In the United States, both racial and socioeconomic factors determine whether individual communities are left behind when it comes to environmental over-sight. While progress has been made in reducing pollution levels over the past few decades, research conducted at the Alfred Weber Institute for Economics suggests that environmental injustice persists: U.S. firms are less likely to be inspected for compliance with environmental standards following increases in the non-White population in the communities where they operate - especially in states where Republican candidates consistently win major elections. As this article shows, moving forward will require a uniform and equitable approach to environmental regulation and enforcement.